Performance and institutional dynamics of the Warehouse Receipt system in Tanzania: Evidence from Agricultural Cooperatives - Benson Ndiege (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the performance and institutional dynamics of the Warehouse Receipt System (WRS) in Tanzania, particularly in cooperative-managed crop markets. The study is important because WRS plays a strategic role in improving agricultural trade, market access, and farmers’ bargaining power, yet its implementation still faces various institutional and operational challenges. Design/methodology/approach – The study employed a mixed-methods approach by combining quantitative and qualitative data. Secondary data on crop production and sales were analyzed statistically, while qualitative information was collected through Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs) to explore administrative, coordination, and institutional issues affecting WRS implementation. Findings/Results – The findings reveal that the WRS has strengthened crop markets by increasing the volume and value of traded crops, especially cash crops such as cashew nuts, sesame, and coffee. The system also improved price stability and market credibility by connecting farmers with potential buyers. However, the benefits were uneven due to administrative weaknesses within cooperatives, power imbalances between buyers and sellers, weak institutional coordination, and limited participation of financial institutions in warehouse receipt financing. Originality/Value – The study concludes that the effectiveness of WRS depends not only on market infrastructure but also on strong institutions, cooperative governance, and stakeholder coordination. The research highlights the importance of improving institutional quality and collaboration among stakeholders to ensure a more inclusive and effective agricultural marketing system in Tanzania.